Peripheral lymphocyte subsets in chronic hepatitis C: Effects of 12 weeks of antiviral treatment with interferon-alpha plus ribavirin. (February 2016) - Oliveira, Isabela S.; Carvalho, Lucas P.; Schinoni, Maria Isabel; Paraná, Raymundo; Atta, Ajax M.; Sousa Atta, Maria Luiza B.
Abstract: Chronic infection with hepatitis C virus (HCV) causes a quantitative and functional alteration in innate and adaptative immunity. In the present work, we determined by flow-cytometry the profile of blood lymphocyte of untreated HCV patients and in subjects of this group that achieved or not an early virologic response at 12-weeks of treatment with interferon-α plus ribavirin. Twenty-six untreated HCV patients and 20 control healthy individuals were enrolled in the study. Untreated HCV patients had a higher proportion of B cell and a lower proportion of CD8 + T cell and NK cells than healthy individuals did, but the proportions of CD4 + T cells and Treg cells (CD4 + CD25 + Foxp3 + ) were similar in these patients and controls. Untreated HCV patients presenting cryoglobulinemia had a lower proportion of Treg cells and a lower Treg/NK cell ratio when compared with those without cryoglobulins. Nineteen out of 26 untreated HCV patients remained in the study and were treated with Interferon-α plus ribavirin. At 12-weeks of treatment, 10 of them achieved early virologic response (EVR), whereas 9 were non-responders (NR). EVR patients differed from NR patients in the increase of their proportion of NK cells at 12 weeks of treatment. In conclusion, untreated HCV patients exhibit an altered profile of blood lymphocyte subsets, including a reduction in the proportion of CD4 + CD25 + FoxP3 + T regulatory cells in patients that present cryoglobulinemia. An early virological response at 12-weeks of treatment with IFN-α plus ribavirin seems to be associated a significant improvement in the proportion of NK cells of HCV treated patients. Highlights: Chronic hepatitis C alters the proportion of peripheral B, CD8 + and NK cells. The proportion of Treg cells is decreased in HCV patients with cryoglobulinemia. An early virologic response is associated with an increased proportion of NK cells.